Specific proliferative T cell responses and antibodies elicited by vaccination with simian immunodeficiency virus Nef do not confer protection against virus challenge. - Wade-Evans, A; Stott, J; Hanke, T; Stebbings, R; Berry, N; Lines, J; Sangster, R; Silvera, P; Walker, B; MacManus, S; Davis, G; Cowie, J; et al. (2001)
The efficacy of immunizing with a combination of simian immunodeficiency virus (SIV) Nef vaccines was evaluated. Four vaccinates received three intradermal immunizations with recombinant vaccinia virus that expressed SIV Nef, followed by three intramuscular immunizations with rDNA also expressing SIV Nef. Finally, the four vaccinates received two subcutaneous boosts with recombinant SIV Nef protein. This immunization protocol elicited anti-Nef antibodies in all of the vaccinates as well as specific proliferative responses. However, specific cytotoxic T cell responses were not detected before virus challenge. All vaccinates were challenged intravenously with 10 MID(50) of SIVmacJ5 along with four controls. All eight subjects became infected after SIV challenge and there were no group-specific differences in virus load as measured by virus titration and vRNA analysis. The results of this study support indirectly the report from Gallimore and colleagues (Nat Med 1995;1:1667) suggesting that CD8(+) T lymphocyte responses are required for Nef-based vaccines to restrict SIV infection. If Nef-based vaccines are to be beneficial in controlling infection with immunodeficiency viruses, then it will be necessary to develop more effective immunization protocols that elicit potent CD8(+) cell responses reproducibly.